Azepanium based protic ionic liquids: Synthesis, thermophysical properties and COSMO-RS study - Dong, Y. (Elsevier B.V., 2018)
Protic ionic liquids (ILs) with seven-membered azepanium cation were synthesized and characterized. The molecular structure of the synthesized ILs was confirmed using 1H NMR and 13C NMR spectroscopy. In one hand, sulfonic acid (âSO3H) group was tethered to the azepanium moiety combined with HSPO4 or H2PO4 âanion and on the other hand azepanium based alkyl sulfate ILs were synthesized by reacting azepane with corresponding dialkyl sulfates. Thermo-physical properties (density, viscosity, glass transition temperature, thermal decomposition temperature) of the synthesized ILs were measured. All the studied ILs showed good thermal stability. From the viscosity and density data of alkyl sulfate ILs, the volumetric properties such as molar volume, lattice energy and standard molar entropy were calculated. COSMO-RS was used to predict hydrogen bonding energy, interaction energy, Van der Waals energy and H-bond accepting and H-bond donating nature of these pure ILs. Activity coefficient values have also predicted for these ILs with cellulose. Â© 2018 Elsevier B.V.